Effect of the interlayer on soil temperature and the transformation between phreatic water and soil water under laboratory freeze-thaw action - Chen, Junfeng; Ren, Jiameng; Wang, Erqing; Cui, Lihong; Xue, Jing; Zheng, Xiuqing; Du, Qi (Frontiers in Earth Science, 2023)
To reveal the effect of interlayer on the temperature of freeze-thaw soil and the transformation between phreatic water and soil water in shallow groundwater areas, a freeze-thaw test was conducted with a groundwater table depth of 0.5 m under laboratory freeze-thaw action. The soil temperature and the transformation between phreatic water and soil water of sand columns under constant freezing temperature at −20°C lasted for 20 days, and the thawing process lasted for 15 days were monitored. The interlayers with a particle size of 0.1–0.5 mm (d50 = 0.3 mm) and a thickness of 5 cm were set at 5 cm, 15 cm, 20 cm, and 25 cm away from the surface and these sand columns were marked as D5, D15, D20, and D25, which were compared with a homogeneous sand column (Ch) with a particle size of 0.5–1.5 mm (d50 = 1.0 mm). The results showed that the fine particle interlayer had thermal insulation on the soil profile and that it effectively inhibited upward migration of phreatic water to soil water during the freezing process. A sand column that had a near-surface interlayer had a better thermal insulation, a stronger inhibition effect on upward migration amount of phreatic water to soil water (UMA) and a larger cumulative downward movement amount of soil water to phreatic water (DMA). The cumulative UMA of D5, D15, D20, and D25 was 61–84% of Ch during the freezing stage, and the cumulative DMA of D5, D15, D20, and D25 was 29–57% of Ch during the thawing stage. The inefficient loss of groundwater increased exponentially with the depth of interlayer, the sand column with an interlayer that was farther away from the surface consumed more groundwater and stored more water in the unsaturated zone, and its DMA reached almost zero earlier. These research results were significant for the scientific evaluation of water resources in shallow groundwater areas.